Configurations of lobed nozzles for high mixing effectiveness. (December 2015) - Sheng, Zhi-qiang; Huang, Pei-lin; Zhao, Tong; Ji, Jin-zu
Highlights: A new alternating-lobe nozzle and two types of lobe-peak spoilers are introduced. The distribution of the primary stream in the jet mixing flow field is obtained. The jet mixing flow field is divided into several regions for analysis. The division of the streamwise vortices into segments is propounded. Mechanisms for the high mixing effectiveness of lobed nozzles are analysed. Abstract: The circular lobed nozzle used in the infrared suppressors of helicopters and warships has a configuration that facilitates highly effective mixing of the jet. A sword alternating-lobe nozzle and two types of spoilers (installed at the lobe peaks to improve the mixing) were introduced. In this study, numerical investigations of the jet mixings of different nozzle configurations were conducted. The nozzles considered were a baseline lobed nozzle, a baseline lobed nozzle with a central plug, a coplanar alternating-lobe nozzle, a sword alternating-lobe nozzle, and a sword alternating-lobe nozzle with lobe-peak spoilers. The dominant factors that affect the pumping performance, mixing effectiveness, and pressure loss were also analysed. It was found that, in addition to the intensity of the streamwise vortices and the distribution of the primary stream, the distribution of the streamwise vortices is also strongly related to the mixing effectiveness and determined the formation of new and plumper streamwise vortices, which improved the mixing effectiveness. The division into three segments of the side of the streamwise vortices on which the primary and secondary streams contact each other is propounded. The three segments are the windward, sideward, and leeward segments. The windward segment has the fastest mixing, followed by the sideward segment, while the leeward segment has the slowest mixing. The plumper streamwise vortices enhance mixing because their windward segment is longer.